New Mycomya species from the Himalayas (Diptera, Mycetophilidae): 3. Subgenera Cesamya and Mycomyopsis - Väisänen, Rauno (Zootaxa, 2013)
Mycomya Rondani specimens from the Himalayas, mostly Nepal and Myanmar, are revised. Altogether four species of the subgenus Cesamya Koçak & Kemal and eleven species of the subgenus Mycomyopsis Väisänen are recorded from the Himalayas and the Indian subcontinent. The paper includes a key to the Himalayan species of Mycomya of the two subgenera. The following fourteen new species are described: M. aix, M. alticola, M. banteng, M. cissa, M. ducula, M. irena, M. goral, M. jeti, M. kaa, M. naja, M. niltava, M. pitta, M. sachak, and M. sanar. The holotype of M. unipectinata Edwards from Sri Lanka was also examined and its genitalia are described.